Radical combustion engine characteristics studies for production engines / Ahmad Suhaimi Abd Rahim and Saqaf Ahmed Alkaff - Abd Rahim, Ahmad Suhaimi; Ahmed Alkaff, Saqaf (2003)
The radical ignition (RI) process also called activated radical (AR) combustion is not exactly new, but only recently have engineers begun to exploit the process in practical power plants. These new units include a lightweight two-stroke racing motorcycle engine, truck diesels with reduced soot output, and lean bum spark ignited car engines. Several engines using radical combustion techniques are being developed today [1]. One in particular is the single cylinder, two-cycle engine that powers the EXP-2 off-road racing motorcycles developed by research engineers at Honda Motor Co. Ltd. in Tokyo [2]. Early on the development of the internal combustion engine, there were indications that something else was going on in fuel combustion. Owners of motorcycles, generators and other two-stroke power machines noticed that under certain unusual circumstances, these engines would "run on", that is it will continue running after the electrical ignition system was shut off. Most engineers had seen two-cycle engines revving away even though there were no sparking inside. They generally attributed this self-ignition phenomenon to pre-ignition caused by hot spots in the combustion chamber and it was generally dismissed without serious study.